1977
DOI: 10.1530/jrf.0.0490069
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive function in prepubertal lambs: ovulation, embryo development and ovarian steroidogenesis

Abstract: However, oestrogen production by lamb follicles immediately after explantation was higher than that of adult follicles and the administration of progesterone to lambs before PMSG treatment decreased subsequent follicular testosterone production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

1978
1978
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
2
9
0
2
Order By: Relevance
“…In the study by Quirke & Hanrahan (1977), for example, the survival rate to term of 8-16-cell eggs from ewe lambs of the Galway breed after transfer to the uteri of adult ewes was less than half that of similar eggs from mature ewes (33 compared with 73%). Because of this and of the evidence of a different pattern of oestrogen secretion by lamb follicles in vitro and in vivo (Trounson, Willadsen & Moor, 1977;Quirke et al, 1981) it has been suggested ) that conditions in the developing follicle or in the reproductive tract between ovulation and the 8-16-cell stage may be related to the reduced fertility of very young ewes. A high frequency of errors of oogénesis or of fertilization, because of maternal age, could also be implicated and a karyotyping study, similar to that by Long & Williams (1980) with mature ewes, could provide useful clues in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Quirke & Hanrahan (1977), for example, the survival rate to term of 8-16-cell eggs from ewe lambs of the Galway breed after transfer to the uteri of adult ewes was less than half that of similar eggs from mature ewes (33 compared with 73%). Because of this and of the evidence of a different pattern of oestrogen secretion by lamb follicles in vitro and in vivo (Trounson, Willadsen & Moor, 1977;Quirke et al, 1981) it has been suggested ) that conditions in the developing follicle or in the reproductive tract between ovulation and the 8-16-cell stage may be related to the reduced fertility of very young ewes. A high frequency of errors of oogénesis or of fertilization, because of maternal age, could also be implicated and a karyotyping study, similar to that by Long & Williams (1980) with mature ewes, could provide useful clues in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…The follicles are able to respond to exogenous gonadotrophins and ovulation may be induced (Mansour, 1959). If intrauterine insemination is used to bypass the cervical block, the eggs ovulated may be fertilized (Land & McGovern, 1968), and when transferred to adults at an appropriate stage of the oestrous cycle they develop normally (Trounson, Willadsen & Moor, 1977). The latter authors also demonstrated that the capacity of the lamb follicle to secrete oestrogen, testosterone and progesterone in vitro was similar to that of the adult.…”
Section: Genetic and Seasonal Variationmentioning
confidence: 97%
“…The reason for this embryonic loss has been suggested to be inadequate gonadotrophic support of the induced CL (Segal and Baker, 1973). Trounson et al (1977) claim that gonadotrophin production in the pre-pubertal sheep should be adequate. The abnormal dividing ova recovered in this experiment may indicate some inadequacy in the ova themselves or some inadequacy in the maternal environment.…”
Section: Yearmentioning
confidence: 99%